2017
DOI: 10.1515/agri-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of operating temperature of gas transit pipeline on soil quality and production potential of crops

Abstract: The aim of this study is to investigate the effects of gas transit pipeline temperature on soil moisture, soil temperature and yield of harvest crops. The study area was located in the village Ivanka pri Nitre (Nitra District, Southwestern Slovakia). Soil type in the site is Orthic Brown Chernozem. Temperature of the transported gas increased the soil temperature in the range of 2.07°C to 3.4°C measured in a depth ranging from 250 mm to 350 mm above the gas lines. The temperature also reduced soil moisture by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Similarly, Halmova et al. (2017) reported winter wheat yields increased over the trench, likely due to warmer soil conditions from pipeline temperatures. These authors reported that winter wheat yields over the trench were higher by 9.4–13.1%, and sunflower yields were higher by 8.1% compared with control areas.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Similarly, Halmova et al. (2017) reported winter wheat yields increased over the trench, likely due to warmer soil conditions from pipeline temperatures. These authors reported that winter wheat yields over the trench were higher by 9.4–13.1%, and sunflower yields were higher by 8.1% compared with control areas.…”
Section: Resultsmentioning
confidence: 87%
“…Halmova et al. (2017) in the Slovak Republic reported the temperature of a transported gas pipeline increased soil temperature above the pipeline 2.1–3.4 °C higher than soils farther away from the pipeline. Comparatively, Shi et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations